Security sector reform in Southeast Asia from policy to practice - Heiduk, Felix (Critical Studies of the Asia Pacific Series, 2014)
Successful reform of the security sector has been regarded as pivotal for a successful transition from authoritarianism to democracy. Contributors examine the so far relatively unexplored theme of Security Sector Reform in Southeast Asia. In an attempt to escape the military-centered approaches dominating contemporary debate this volume examines a wide selection of policy fields, touching on different aspects of SSR such as local ownership, executive and legislative control of security forces, gender mainstreaming, the role of civil society organizations, and the commercialization of security services. Bridging the gap between academics and practitioners, the book brings together diverse perspectives on security sector related reforms in Southeast Asia and their possible future developments